Pelatihan Pengelolaan Kelas Daring Berbasis Aplikasi Google Classroom dan Edpuzzle di SMP PGRI 5 Denpasar Bali - Dewi, Eka Grana Aristyana; Putri, I Gusti Agung Pramesti Dwi (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this service activity is to improve the ability of teachers at SMP PGRI 5 Denpasar in managing online classes by providing online class management training based on the Google Classroom and Edpuzzle applications. The method of implementing this activity is lecture, practice, and discussion. Lectures were conducted to deliver material on the stages of classroom management using Google Classroom and using videos on Edpuzzle. The participants of this activity were all teachers of SMP PGRI 5 Denpasar totaling 40 people. For online class management, participants were given training in class management and grades, using forums, and making materials and quizzes. For the use of videos as learning materials, participants were training in choosing videos, editing videos, inserting messages and questions as well as multiple choices. The results of this service activity are as many as 72,5% of participants have been able to manage online classes and integrate with Edpuzzle. Partners have also agreed to use Google Classroom and Edpuzzle for learning for the 2021/2022 academic year.